2012
DOI: 10.2174/157015912804499429
|View full text |Cite
|
Sign up to set email alerts
|

Redox Processes in Neurodegenerative Disease Involving Reactive Oxygen Species

Abstract: Much attention has been devoted to neurodegenerative diseases involving redox processes. This review comprises an update involving redox processes reported in the considerable literature in recent years. The mechanism involves reactive oxygen species and oxidative stress, usually in the brain. There are many examples including Parkinson's, Huntington's, Alzheimer's, prions, Down's syndrome, ataxia, multiple sclerosis, Creutzfeldt-Jacob disease, amyotrophic lateral sclerosis, schizophrenia, and Tardive Dyskines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 92 publications
(96 reference statements)
1
15
0
2
Order By: Relevance
“…However, advanced aging, genetic mutations or long-term environmental exposure could accelerate the production of ROS, which activates pro-apoptotic signalling or inhibits pro-survival signal and finally leads to cell death [48][49][50][51]. However, advanced aging, genetic mutations or long-term environmental exposure could accelerate the production of ROS, which activates pro-apoptotic signalling or inhibits pro-survival signal and finally leads to cell death [48][49][50][51].…”
Section: Dj-1 and Rack1 Were Correlatively Decreased In The Cellular mentioning
confidence: 99%
“…However, advanced aging, genetic mutations or long-term environmental exposure could accelerate the production of ROS, which activates pro-apoptotic signalling or inhibits pro-survival signal and finally leads to cell death [48][49][50][51]. However, advanced aging, genetic mutations or long-term environmental exposure could accelerate the production of ROS, which activates pro-apoptotic signalling or inhibits pro-survival signal and finally leads to cell death [48][49][50][51].…”
Section: Dj-1 and Rack1 Were Correlatively Decreased In The Cellular mentioning
confidence: 99%
“…The pathogenesis of neurological disorders is still not clearly identified, and oxidative stress in neuronal cell has been proposed to play roles in disease processes [12]. The oxidative stress status of cell and tissue could be altered by exposure to oxidants.…”
Section: Introductionmentioning
confidence: 99%
“…). Studies have also shown that QA may form complexes with iron and electron transfer from these complexes to oxygen result in increased ROS production (Guillemin ; Kovacic and Ratnasamy ). QA–Fe 2+ complexes may also initiate the Fenton reaction in which highly reactive hydroxyl radicals are formed (Guillemin ).…”
Section: Resultsmentioning
confidence: 99%